Ketersediaan dan Pemanfaatan Buku Cerita Rakyat Kalimantan Tengah dalam Pembelajaran SD di Kecamatan Kahayan Tengah, Kabupaten Pulang Pisau - Nirena Ade Christy; Syarah Veniaty; Yulina Mingvianita; Stefani Ratu Lestariningtyas; Ibnu Yustiya Ramadhan; Jumadi Jumadi; Hana Pertiwi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study describes the availability and utilization of Central Kalimantan folklore books in elementary school learning in Kahayan Tengah District, Pulang Pisau Regency. Folklore has potential as a contextual learning medium that strengthens students' character and cultural literacy. The research employed a descriptive qualitative approach with observation, in-depth interviews, and documentation in three randomly selected elementary schools: SDN Tuwung 1, SDN Tuwung 2, and SDN Bukit Rawi 1. The findings reveal that the availability of Central Kalimantan folklore books is uneven. SDN Tuwung 1 possesses several bilingual books from the Central Kalimantan Language Center. SDN Bukit Rawi 1 has only two anthology titles in fairly good physical condition. SDN Tuwung 2 has only one local folklore book. The utilization of folklore books in learning remains incidental and has not been systematically integrated into the curriculum. The most frequently used methods are read-aloud and oral storytelling. Follow-up activities such as rewriting or dramatization are rarely conducted. The main challenges include limited book collections, lack of curriculum integration, and minimal teacher training. Nevertheless, students' enthusiasm for folklore is considerably high, indicating significant opportunities to develop literacy programs based on Central Kalimantan folklore. This study recommends more equitable book collection provision, integration of folklore into learning modules, and teacher training to innovatively utilize folklore in the learning process.